Visualizing Localized Reentry With Ultra-High Density Mapping in Iatrogenic Atrial Tachycardia Beware Pseudo-Reentry - Luther,V; Sikkel,M; Bennett,N; Guerrero,F; Leong,K; Qureshi,N; Ng,FS; Hayat,SA; Sohaib,SMA; Malcolme-Lawes,L; Lim,E; Wright,I; et al. (CIRCULATION-ARRHYTHMIA AND ELECTROPHYSIOLOGY, 2017)
Background—The activation pattern of localized reentry (LR) in atrial tachycardia remains incompletely understood. We used the ultra–high density Rhythmia mapping system to study activation patterns in LR.Methods and Results—LR was suggested by small rotatory activations (carousels) containing the full spectrum of the color-coded map. Twenty-three left-sided atrial tachycardias were mapped in 15 patients (age: 64±11 years). 16 253±9192 points were displayed per map, collected over 26±14 minutes. A total of 50 carousels were identified (median 2; quartiles 1–3 per map), although this represented LR in only n=7 out of 50 (14%): here, rotation occurred around a small area of scar (<0.03 mV; 12±6 mm diameter). In LR, electrograms along the carousel encompassed the full tachycardia cycle length, and surrounding activation moved away from the carousel in all directions. Ablating fractionated electrograms (117±18 ms; 44±13% of tachycardia cycle length) within the carousel interrupted the tachycardia in every LR case. All remaining carousels were pseudo-reentrant (n=43/50 [86%]) occurring in areas of wavefront collision (n=21; median 0.5; quartiles 0–2 per map) or as artifact because of annotation of noise or interpolation in areas of incomplete mapping (n=22; median 1, quartiles 0–2 per map). Pseudo-reentrant carousels were incorrectly ablated in 5 cases having been misinterpreted as LR.Conclusions—The activation pattern of LR is of small stable rotational activations (carousels), and this drove 30% (7/23) of our postablation atrial tachycardias. However, this appearance is most often pseudo-reentrant and must be differentiated by interpretation of electrograms in the candidate circuit and activation in the wider surrounding region.